Risk of venous thromboembolism with rheumatoid arthritis - Matta, Fadi; Singala, Ravinder; Yaekoub, Abdo Y.; Najjar, Reiad; Stein, Paul D. (Thrombosis and Haemostasis, 2009)
Rheumatoid arthritis is not generally considered to be a risk factor for venous thromboembolism (VTE), although abnormalities of coagulation factors have been found in patients with rheumatoid arthritis. Sparse data in a few patients suggest that patients with rheumatoid arthritis may have higher rates of VTE. The purpose of this investigation was to determine if the incidences of pulmonary embolism (PE) and deep venous thrombosis (DVT) are increased in hospitalized patients with rheumatoid arthritis. The number of patients discharged from non-Federal short-stay hospitals throughout the United States from 1979 through 2005 with a discharge code for rheumatoid arthritis was obtained from the National Hospital Discharge Survey (NHDS). Among hospitalized patients with rheumatoid arthritis who did not have joint surgery, 41,000 of 4,818,000 (0.85%) had PE compared with 3,366,000 of 891,055,000 (0.38%) among patients who did not have rheumatoid arthritis and who did not have operations or joint surgery (relative risk =2.25). Deep venous thrombosis was diagnosed in 79,000 of 4,818,000 (1.64%) patients with rheumatoid arthritis and no joint operation, versus 7,681,000 of 891,055,000 (0.86%) who did not have rheumatoid arthritis or a joint operation (relative risk=1.90). The relative risk of venous thromboembolism (PE and/or DVT) in these patients was 1.99. The data suggest that rheumatoid arthritis is a risk factor for VTE in hospitalized medical patients. A heightened awareness of the risks for VTE and a lower threshold for evaluation of patients for possible DVT or PE would be appropriate in caring for hospitalized patients with rheumatoid arthritis.
Keywords: Pulmonary embolism; deep venous thrombosis; venous thromboembolism; rheumatoid arthritis